Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/1477-5956-8-46
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic- and extracellular-proteome analysis of Diplodia seriata: a phytopathogenic fungus involved in grapevine decline

Abstract: BackgroundThe phytopathogenic fungus Diplodia seriata, whose genome remains unsequenced, produces severe infections in fruit trees (fruit blight) and grapevines. In this crop is recognized as one of the most prominent pathogens involved in grapevine trunk disease (or grapevine decline). This pathology can result in the death of adult plants and therefore it produces severe economical losses all around the world. To date no genes or proteins have been characterized in D. seriata that are involved in the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 63 publications
2
54
0
Order By: Relevance
“…Moreover, Luini et al (2010) hypothesised that the secreted proteins of Pch and Pal, associated with esca disease, modify plant cell (V. vinifera 41 B cells) metabolism and may act as virulence factors. A report on the extracellular proteome analysis of D. seriata has shown 75 secreted proteins between 12 and 84 kDa (Cobos et al 2010). Only 16 proteins have been identified, including 3 necrosis-and ethylene-inducing proteins (Nep) at 26.0, 33.8 and 35.7 kDa (Cobos et al 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, Luini et al (2010) hypothesised that the secreted proteins of Pch and Pal, associated with esca disease, modify plant cell (V. vinifera 41 B cells) metabolism and may act as virulence factors. A report on the extracellular proteome analysis of D. seriata has shown 75 secreted proteins between 12 and 84 kDa (Cobos et al 2010). Only 16 proteins have been identified, including 3 necrosis-and ethylene-inducing proteins (Nep) at 26.0, 33.8 and 35.7 kDa (Cobos et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Some of these proteins have been identified as virulence factors in Nectria haematococca and Sclerotinia sclerotiorum but their contribution to pathogenicity was not precisely analysed (Cobos et al 2010). Ramirez-Suero et al (2014) demonstrated that the total extracellular compounds produced by N. parvum were more aggressive on calli than those of D. seriata and produced higher amounts of mellein.…”
Section: Introductionmentioning
confidence: 98%
“…This approach has frequently been applied in fungi to elucidate the proteome and secretome under various conditions including plant-pathogen interactions (27,28). Using this technology, however, only limited information has been gained in Phytophthora.…”
mentioning
confidence: 99%
“…In spite of this fact, several fungi which are producers of severe infections in fruit trees (fruit blight) and grapevines, like Diplodia seriata, keep fully unsequenced. Despite this limitation, 2D electrophoresis application combined with de novo sequencing and BLAST similarity search by a 4800 MALDI-TOF/TOF Analyzer (Applied Biosystems) led to the protein identification of virulence factors described in other fungal strains when they grew in medium supplemented with carboxymethyl cellulose (Cobos et al, 2010). This fact shows the wide range of Proteomics applications.…”
Section: The Environment and Fungal Secretomesmentioning
confidence: 99%
“…Thus, the use of liquid nitrogen to decrease warming of the disruption systems is a widely used method. The main cell-breaking system is the traditional pre-chilled mortar grinding due to its efficiency against the fungal cell wall (Cobos et al, 2010;Lu et al, 2010;Vödisch et al, 2011), although waring blender machines (Lim et al, 2001), or glass bead beating systems, either combined with a 10 mM Tris-HCl buffer (Oh et al, 2010) or with a phenol buffer (Coumans et al, 2010;Vodisch et al, 2011), have been successfully applied. After the breaking step, the protein solubilisation buffer always includes a protease inhibitor [e.g.…”
Section: Proteomics a Useful Tool For The Analysis Of Fungimentioning
confidence: 99%